Risks and opportunities from key importers pushing for sustainability: the case of Indonesian palm oil - Yaghoob Jafari; Jamal Othman; Peter Witzke; Sufian Jusoh (Agricultural and Food Economics, 2017)
Growing concerns in the major importing countries on the socio-environmental sustainability of oil palm farming may affect the import demand of palm oil and hence the economy of the exporting countries. This paper develops a comparative static, partial equilibrium model to examine the impact of potential reductions in EU imports of Indonesia's palm oil on palm oil output, prices, factor markets, trade, deforestation, and peatland conversion in Indonesia. Results suggest that there would be only small impacts on the major environment-economic variables in Indonesia in a scenario with a moderate reduction EU import demand, for example, due to sustainability concerns. However, the impacts would be more profound if sustainability concerns also affect other import regions and trigger a similar decline in import demand in other markets. The way forward for Indonesia and other palm oil producers and exporters is to adopt a common set of sustainability criteria, encompassing the elements of transparency, regulatory compliance, best agricultural practices, environmental responsibility, the livelihood of small farmers, as well as human and community rights.
Keywords: Q17; Q18; Q51; Q56; 330; Sustainable palm oil; Agricultural trade policy; Sustainability criteria; Forest conversion for oil palm; Trade-environment linkages; Indonesia